Análisis de la utilización de derivados financieros en las empresas no financieras mexicanas y su efecto en las cotizaciones bursátiles - José Asunción Corona Due\~nas (Atlantic Review of Economics, 2012)
– In this paper we study the possible effect it may have concerning the use of financial derivatives in the evolution of the share price of Mexican non-financial corporations, whether such contracts are used for hedging financial risks or for trading. The first part is a review of the literature to analyze work they have done to date others, then studied at 25 non-financial companies listed on the Mexican Stock Exchange and are part of the Price Index and Quotes. Using a statistical model has been contrasted and tested the hypothesis, confirming that the use of financial derivatives has a significant positive influence on stock prices of companies.
Keywords: G12; G13; G15; 330; Finanzderivat; Börsenkurs; Mexiko